2007
DOI: 10.2353/ajpath.2007.070075
|View full text |Cite
|
Sign up to set email alerts
|

Synaptopodin Protects Against Proteinuria by Disrupting Cdc42:IRSp53:Mena Signaling Complexes in Kidney Podocytes

Abstract: The actin-based foot processes of kidney podocytes and the interposed slit diaphragm form the final barrier to proteinuria. Mutations affecting several podocyte proteins cause disruption of the filtration barrier and rearrangement of the highly dynamic podocyte actin cytoskeleton. Proteins regulating the plasticity of the podocyte actin cytoskeleton are therefore of critical importance for sustained kidney barrier function. Synaptopodin is an actin-associated protein essential for the integrity of the podocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 48 publications
(111 reference statements)
6
149
0
6
Order By: Relevance
“…Interestingly, the SH3 domain of IRSp53 has been shown to mediate the interaction with Eps8 and to enhance Eps8-Abi1-Sos-1 signaling to Rac1 (Funato et al, 2004). More recently, Yanagida-Asanuma and colleagues showed that synaptopodin, an actin-associated protein, binds directly to IRSp53 and suppresses Cdc42-IRSp53-Mena-initiated formation of filopodia by blocking the binding of Cdc42 and Mena to IRSp53 in kidney podocytes (Yanagida-Asanuma et al, 2007). This suggests that the interactions of IRSp53 alone are complex and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the SH3 domain of IRSp53 has been shown to mediate the interaction with Eps8 and to enhance Eps8-Abi1-Sos-1 signaling to Rac1 (Funato et al, 2004). More recently, Yanagida-Asanuma and colleagues showed that synaptopodin, an actin-associated protein, binds directly to IRSp53 and suppresses Cdc42-IRSp53-Mena-initiated formation of filopodia by blocking the binding of Cdc42 and Mena to IRSp53 in kidney podocytes (Yanagida-Asanuma et al, 2007). This suggests that the interactions of IRSp53 alone are complex and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these patients do respond to treatment with corticosteroids plus CsA. In these cases, it is interesting to note that the targets of CsA in glomerular disorders are not only T-or Bcells but also the podocyte cytoskeleton via inhibition of synaptopodin phosphorylation [14]. Stabilization of the cytoskeleton might be the explanation for the effects of add-on CsA observed in the APN CsA study [9].…”
Section: Limitations Of the Saadeh Studymentioning
confidence: 99%
“…43 In addition, Asanuma et al demonstrated that synaptopodin plays an essential role in the formation of focal contacts via the inhibition of Smurf1-mediated polyubiquitination of RhoA. 38 Specifically, targeted synaptopodin gene knockdown in podocytes promoted derangement of focal contact assembly, podocyte dysmotility, and enhanced RhoA polyubiquitination.…”
Section: R394tmentioning
confidence: 99%